Little Journey: a phase III randomised controlled trial of a psychological preparation and education smartphone application for management of paediatric perioperative anxiety compared with standard care in children undergoing ambulatory surgery – study protocol - Gareth Ambler; Daisy Fancourt; Chris Brew-Graves; Norman R Williams; Monty Mythen; Matthew Wilson; Mark Emberton; Mohini Samani; Matthew Fenton; Suneetha Ramani Moonesinghe; Christopher Evans; Georgia Bercades; et al. (BMJ Open)
Introduction Children having surgery, and their parents, commonly have anxiety in the preoperative period, and this may impact longer-term health and quality of life. Psychological preparation can be expensive and time-consuming, and the type and effectiveness of preparatory interventions are variable. The aim of this randomised controlled trial (RCT) is to evaluate the clinical effectiveness of a preoperative smartphone psychological preparation application with virtual reality (VR) capability (the ‘Little Journey app’ (LJ)), at reducing anxiety and its sequelae in children and their carers.Methods and analysis Multicentre, assessor-blinded, two-armed, parallel group, RCT in children aged between 3 and 12 years, undergoing ambulatory surgery and receiving their first general anaesthetic. Randomisation is one-to-one between an intervention and a control arm. Participants in the intervention arm are provided with access to the LJ app and a low-cost cardboard VR headset (to be used with a smartphone) to use in the weeks leading up to their operation. Children in the control arm receive the same VR headset and suggestions of unrelated VR games to play, but no access to the LJ app. To improve accessibility, smart devices are provided to children whose families do not have a smart phone, and the app content has been translated from English into multiple languages. Both groups receive standard perioperative care at the hospital where they are having treatment. The primary outcome measure is the modified Yale Preoperative Anxiety Scale-Short Form applied by independent blinded observers, immediately before induction of general anaesthesia. Secondary outcomes include process measures, psychological and socioeconomic outcomes for both children and parents/carers. The planned sample size was 304 participants, including an anticipated 15% attrition rate. An interim analysis was conducted when the trial was temporarily paused because of the COVID-19 pandemic, at which point 119 participants had been recruited. The trial steering committee and data monitoring committee recommended continuation of the trial, but the sample size was increased to 596 to account for differences between the previously anticipated and actual outcomes of recruited participants.Ethics and dissemination The study was approved by Surrey Borders—Research Ethics Committee 251219, and all participating sites were in England. Results will be presented in academic manuscripts and presentations and summarised for diverse audiences (including clinicians and patients/public) in podcasts, infographics and other multimedia formats.Trial registration number NCT03797716.